Prediksi Harga Saham Harian PT BTPN Syariah Tbk Menggunakan Model Arima dan Model Garch - Muhammad Iqbal; Nur Wahyu Ningsih (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to find the ARIMA Model and GARCH Model which had the best performance in predicting the stock price of PT. BTPN Syariah Tbk. The method of data collection and analysis uses the Box and Jenkins method which uses an iterative approach. Meanwhile, data processing is assisted by the E-Views software application. The results of the study obtained that model A model ARIMA (p,d,q) the best model chosen was ARIMA (1,1,1). Based on the estimation results and the selection of the best model, the best selected model is GARCH (2,1) so that the mean equation Yt = 0.001193 + et and the variance equation _t^2 = 0.988415ε_(t-1)^2 + 1.004447ε_ (t-2)^2 -1.001916a_(t-1)^2. The GARCH (1,1) model is able to predict BTPS daily stock price data well for the next one month period, because the forecast data is close to the actual data. This is reinforced by the MAPE value of 1.273%.